The proposed adjustment of Germany's renewable energy law: A critical assessment - Jochen Diekmann; Claudia Kemfert; Karsten Neuhoff (DIW Economic Bulletin, 2012)
Support through the German Renewable Energy Sources Act (EEG) has led, in the past few years, to an unexpectedly wide expansion of systems for generating solar power (photovoltaics) because the system prices for photovoltaic (PV) systems have fallen at a faster rate than the solar power feed-in tariffs guaranteed by the law. This has also contributed to a substantial increase in the EEG surcharge to be paid by consumers. Also in order to slow down the rise in the surcharge, the federal German government has rapidly agreed on major changes to its support for solar power. The article critically reviews the elements of the initial legal proposal by the coalition government, concluding that proposed reductions of the expansion course for photovoltaic capacities are too extreme, the one-off reduction of the solar power feed-in tariffs is at least in parts too drastic, the envisaged rigid future degression of the tariffs is incompatible with market dynamics, and the model for integrating power from renewable energy sources into the market has not been properly thought through. An accompanying innovation strategy should also be considered.
Keywords: O30; O31; Q42; Q48; 330; feed-in tariff; photovoltaic; renewable energy